A journal Systems of Moderation and Sociology of Religion: In Buddhism (Buddhism): Bahasa Indonesia - Ramadhani, Muhammad Iqbal (Maliki Interdisciplinary Journal, 2025)
The concept of religious moderation refers to a perspective that prioritises balance, justice and moderation in religious practice, whether in the form of extreme right or left. This approach is particularly important in the context of a diverse society such as Indonesia, which consists of various ethnicities, cultures and beliefs. Buddhism, through the principle of the Middle Way (Majjhima Patipada), provides a philosophical foundation for realising religious moderation by emphasising values such as love (metta), compassion (karuna), happiness for the happiness of others (mudita), and inner peace (upekkha).Historically, Buddhism has demonstrated its commitment to tolerance and interfaith harmony. This can be seen from the Buddha's attitude of always respecting other beliefs and rejecting all forms of religious coercion. Concrete examples can be found in the policies of King Asoka in India and Buddhist kingdoms in the archipelago such as Srivijaya and Majapahit, which applied the principles of inclusiveness and respect for differences. To develop an attitude of religious moderation, Buddhists are invited to practice Brahma Vihara (four noble qualities) and implement the Eightfold Middle Way, which includes